Comparative study of type 1 tympanoplasty with and without gelfoam in the middle ear - Malick, Nabeel; Gadag, Raveendra P.; K. M., Vidyashree; Puthukulangara, Shruthi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Chronic suppurative otitis media is a widespread disease with a significant cause of morbidity with a greater burden in the poor communities of the developing countries for which tympanoplasty is frequently undertaken. Gelfoam may show detrimental effects such as adhesions and fibrosis and improper packing may physically alter the structure of the tympanic membrane leading to failure of tympanoplasty. The graft can be placed without any middle ear supporting agent wherein the graft is held in position by the surface tension between the novel graft placed and the remnant tympanic membrane. This provides the added advantage of facilitating middle ear ventilation through the Eustachian tube. The objectives of the study were to assess the graft uptake and hearing improvement following type 1 tympanoplasty with gelfoam in the middle ear and without gelfoam in the middle ear and to compare and assess results for complications Methods: This was a randomised control trial done for a period of one year conducted in the department of otorhinolaryngology and head and neck surgery, Karnataka Institute of Medical Sciences, Hubballi which is a tertiary referral hospital. 30 patients underwent type 1 tympanoplasty without gelfoam in the middle ear and 31 patients underwent type 1 tympanoplasty with gelfoam in the middle ear. Post-operative follow up was done to look for graft uptake, hearing assessment by pure tone audiometry and impedance audiometry was done 90 days post-operatively. Results: Graft uptake was 80% in type 1 tympanoplasty without gelfoam in the middle ear and 80.6% with gelfoam in the middle ear. Both types of surgeries had significant hearing improvement, and complications like retraction and residual perforation were also comparable. Ad type of impedance curve is most common post operatively. Conclusions: Graft uptake is equally good in cases with gelfoam and without gelfoam. Hearing gain is comparable in both groups of patients. No significant complications occurred in our study. ‘Ad’ is the most common type of impedance curve after surgery. Long term follow up is important in these patients.